Genetic polymorphism of kappa-casein gene in Friesian Holstein: a basic selection of dairy cattle superiority - Volkandari, S. D.; Indriawati, I.; Margawati, E. T. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
Caseins are milk protein subdivided into four main groups which are αS1, αS2, β-casein and kappa-casein (CSN3). Kappa-casein gene influences the manufacturing of milk properties. The aim of this study was to identify the kappa-casein gene polymorphism in Friesian Holstein (FH) cattle. Fifty nine (59) samples consisted of 32 (Malang), 10 (Sukahati Bogor) and 17 (Research Center for Biotechnology-Indonesian Institute of Sciences’s collections)were applied in this study. DNA samples were extracted by high concentrated NaCl and quantified by spectrophotometer. The kappa-casein gene was amplified at 379 bp fragment by PCR method using a pair primer of kappa-casein at 56oC annealing for 30 cycles. PCR-RFLP technique with HindIII was used for genotyping analysis. The result showed that there were three variants of genotypes (AA, AB and BB) in two populations from Malang and RC for Biotechnology-LIPI’s collection while cattle from Sukahati had only AA and AB genotypes. The averages of genotype frequencies were 65.28%; 65.28%; and 3.00% for AA, AB and BB genotypes respectively while frequencies of 0.81 and 0.19 were for A and B alleles, respectively. FH cattle populations were in equilibrium genetics. This finding concludes that polymorphism was found in three of FH populations with A allele was more common in kappa-casein locus. B allele is known having association with milk production, milk component and cheese yield. Increasing of B allele would influence on milk performance of FH cattle. Explorations of quantitative, qualitative and molecular genetics are important to improve dairy cattle performance.